PENGETAHUAN KEWIRAUSAHAAN DENGAN MOTIVASI DAN NIAT MENJADI ENTREPRENEURS PADA MAHASISWA KEPERAWATAN - Haque, Syafira Daviyatul; Rahman, La Ode Abdul; Rizky, Wahyu; Alviana, Fifi (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Entrepreneurship education has an important role in increasing entrepreneurial knowledge. Entrepreneurship education is given to nursing students through the Entrepreneurship Course. It is intended to encourage the spirit of independence for the nursing profession in the future. The purpose of this study is to find out the relationship between entrepreneurship knowledge with motivation and intention to become entrepreneurs in nursing students. This research is a correlation descriptive study with an observational design (non-experimental). The technique used is stratified random sampling and simple random sampling with a total of 163 student respondents. In addition, there is a significant relationship between entrepreneurship knowledge with motivation and intention to become entrepreneurs in nursing students. Furthermore, the results of this study are expected to be useful for students or nurses in improving the quality of entrepreneurship education in nursing students, especially in fostering motivation and intention to become entrepreneurs for nursing students.